La patria de Pausanias (Notas de lectura a Paus. V, 13, 7): Magnesia del Sípilo y Esmirna - Sánchez Hernández, Juan Pablo (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
This article focuses on Habicht’s interpretation on Paus. V, 13, 7 in his work Pausanias und seine Beschriebung Griechenlands, (Munich:1985), who argues that Magnesia ad Sipylum in Lydia was Pausanias’ birthplace. However, other quotations from Pausanias’ Periegesis in comparison to Epigraphy and Archaeology point to Smyrna as the main cultural and administrative center of the Second Sophistic to which Pausanias would be more related.